Candidates for Mayor of San Jose. - Sahl, Ted (photographer):::Creator::::::::::::
Candidates for mayor of San Jose appear at the Billy DeFrank Lesbian and Gay Community Center. Left-to-right are: Jo-Lynn Otto, DeFrank Program Director, Ron Gonzales, Kathy Chavez and Bill Chew.